Pemberdayaan Ibu Hamil dalam Persiapan Menyusui melalui Pelatihan Teknik Menyusui yang Benar Menggunakan Video Edukasi Sebagai Media Komunikasi Efektif di Kecamatan Aluh-Aluh Kabupaten Banjar - Siti Fatimah; Darmayanti Wulandatika; Mahfuzhah Deswita Putri; Rr. Sri Nuriaty Masdiputri; Noor Anisa; Nelly Mariati (Lembaga Pengembangan Kinerja Dosen, 2024)
Breast milk is an excellent source of nutrition for infants, providing a balanced composition that meets their growth needs. In several regions of South Kalimantan, the coverage of exclusive breastfeeding remains low. In Banjar Regency, the coverage of exclusive breastfeeding reached 82.1% in 2020. Failure to provide exclusive breastfeeding can potentially lead to nutrient deficiencies in infants. This community service aims to enhance knowledge about proper breastfeeding techniques to raise awareness and prepare mothers for breastfeeding before childbirth. Implementation Method: This activity employs training, Q&A sessions, and group viewing of educational videos on proper breastfeeding techniques. Results and Conclusions: The activity led to an increase in knowledge and skills regarding proper breastfeeding techniques. The participants consisted of 15 pregnant women. Among all respondents, the pre-test results showed that the understanding and skills in proper breastfeeding techniques were at 54%. After the post-test, the respondents' understanding increased to 72%, reflecting an 18% improvement. It is hoped that this community service will be beneficial and help in realizing a healthy and intelligent generation through optimal breastfeeding.